Kanglexin protects against cardiac fibrosis and dysfunction in mice by TGF-β1/ERK1/2 noncanonical pathway - Liu, Xue; Han, Weina; An, Na; Cao, Na; Wu, Tingting; Yang, Shuang; Ding, Lili; Chen, Xiaoli; Chen, Chao; Aruhan,; Zhang, Yannan; Wang, Kexin; et al. (Frontiers in Pharmacology, 2021)
Cardiac fibrosis is a common pathological manifestation accompanied with various heart diseases, and anti-fibrotic therapy is an effective strategy to prevent diverse pathological processes of cardiovascular system. We currently report the rational design, synthesis and pharmacological evaluation of a novel anthraquinone compound (1,8-dihydroxy-6-methyl-9,10-anthraquinone-3-oxy ethyl succinate) named Kanglexin (KLX), as a potent cardioprotective agent with anti-fibrosis activity. Our results demonstrated that administration of KLX by intragastric gavage alleviated cardiac dysfunction, hypertrophy, and fibrosis induced by transverse aortic constriction (TAC) surgical operation. Meanwhile, KLX administration relieved endothelial to mesenchymal transition of TAC mice. In TGF β1 treated primary cultured adult mouse cardiac fibroblasts (CFs) and Human umbilical vein endothelial cells (HUVECs), KLX inhibited cell proliferation and collagen secretion. Also, KLX suppressed the transformation of fibroblasts to myofibroblasts in CFs. Further studies revealed that KLX-mediated cardiac protection was due to the inhibitory role of TGF-β1/ERK1/2 noncanonical pathway. In summary, our study indicates that KLX attenuated cardiac fibrosis and dysfunction of TAC mice, providing a potentially effective therapeutic strategy for heart pathological remodeling.